Pelatihan Pembuatan Sabun Cuci Piring Cair Bahan Alami di SMP Riyahotul Arifin Banyuasin, Sumatera Selatan - Ike Purnamasari; Marlina Ummas Genisa; Astrid Sri Wahyuni Sumah; Gunawan Ismail (I-Com: Indonesian Community Journal, 2023)
Soap is a cleaning agent commonly used in daily life, especially for Riyadhotul Arifin Junior High School students who live in the school dormitory (pondok). This community service (PkM) aims to provide training in making dish soap by utilizing pandanus and orange leaves around the school. The PkM method is in the form of mentoring 16 students through direct practice of making liquid soap, discussion, and closing. The high enthusiasm of students during the manufacturing process and the presentation of the results of the liquid dish soap that has been produced are evidence of the achievement of the PkM carried out. Similar activities can be an input for other boarding schools.